Razvoj slovenske države blaginje - Novak, Mojca (Teorija in praksa, 1996)
Theoretically, a few characteristic European welfare-state models can be discerned but the major differentiation is drawn between Western and Eastern models. Moreover, those from the Eastern part of Europe are univocally labelled as "socialist" models by means of which the Communist regimes assured social security "from cradle to grave". However, particular categories,such as industrial workers and those who were politically loyal, had an exclusive access to welfare, solely. Certain new properties come out, if analysing the development of Western and Eastern - "socialist" - models in comparative perspective. It becomes clear that any welfare state model and related social policy was the outcome of different influences. Exogenous initiative of change gives frequently an initial "push" to indigenous efforts and helps to articulate needs. Tradition, power of certain social classes and interests of the political elite provide the indigenous fundament for implementing the welfare idea. Hence, the Slovene model of welfare state should be (re)considered in this respect, as well. As the historical empirical evidence proves, the label of "industrial achievement" the welfare state model fits its properties. Further, they bring it close to those models where the Bismarckian type of welfare has supreme place and influence. Moreover, the Bismarckian ideas of welfare substantially affected through its hundred years development history any model, but particularly in recessions.
Keywords: Europe; Evropa; Slovenia; Slovenija; država blaginje; socialna politika; tranzicija